Intelligence and executive function are associated with age at insult, time post-insult, and disability following chronic pediatric acquired brain injury - Brandt, Anne Elisabeth; Rø, Torstein B.; Finnanger, Torun G.; Hypher, Ruth E.; Lien, Espen; Lund, Bendik; Catroppa, Cathy; Andersson, Stein; Risnes, Kari; Stubberud, Jan (Frontiers in Neurology, 2024)
Background: Pediatric acquired brain injury (pABI) frequently results in lasting cognitive deficits, including IQ and executive functions (EFs). Low age at insult is associated with persistent and debilitating deficits, affecting daily-life functioning negatively. Other developmental factors may relate to cognitive outcomes and performance at different functional levels. We aim to assess how age at insult and time post-insult are associated with IQ and EFs in the chronic phase (>1 year) of pABI, and assess cognitive performance at different levels of global function in daily life. Method: The study utilizes insult information and baseline data from a multicenter RCT, including medical and neuropsychological assessments of participants aged 10 to 17 years with pABI and parent-reported executive dysfunctions. Associations between both age at insult (early, EI; ≤ 7y vs late, LI; > 7y) and time post-insult with IQ and EFs (updating, shifting, inhibition, and executive attention) are examined. Additionally, we explore cognitive performance at different levels of global function according to the Pediatric Glasgow Outcome Scale-Extended. Results: Seventy-six participants (median 8 years at insult, 5 years post-insult), most with moderate disability (n = 38), were included. IQ, executive attention, and shifting were better in LI compared to EI, (adjusted mean differences with 95% Confidence Intervals (CIs); 7.9 (1.4, 14.4), 2.48 (0.71, 4.24) and 1.73 (0.03, 3.43) respectively. Longer time post-insult was associated with poorer performances (mean differences with 95% CIs compared to 1-2 years post-insult for; IQ -11.1 (-20.4, -1.7), -8.4 (-16.7, -0.1), updating -2.6 (-4.4, -0.7), -2.9 (-4.5, -1.2), shifting -3.8 (-6.4, -1.3), -2.6 (-4.98, -0.3) and executive attention -3.2 (-5.7, -0.8). Global function was strongly associated with IQ and EFs, displaying a dose-response relationship with normal range results for good recovery and the poorest performances for severe disability. Conclusions: Early insults and longer time post-insult are associated with poorer cognitive performance following chronic pABI. Also, global function may be a helpful tool to identify the need for cognitive rehabilitation. Although confirmation is needed by larger studies, these findings may inform rehabilitation treatment decisions suggesting particular attention to early insults and to include disability screening in identifying needs for long-term follow-up.